Desain Logo Untuk Peningkatan Identitas Visual Pada UMKM Lesehan 12 Sirah Kencong - Nur Aida Lisurur; Ika Korika Swasti (Pakis Journal Institute, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy by generating employment and business opportunities. However, many MSMEs overlook the importance of visual identity, especially logos, in enhancing competitiveness in the era of globalization. This research focuses on Warung Lesehan 12 in Kebun Bantaran, Blitar, which lacks visual identity. Combining observation and interviews, this study aims to improve visual identity through effective logo design. The establishment, located in an agro-tourism area, has the potential to attract tourists but lacks visual branding. By designing a logo in the form of a white circle with brown elements, including contact information, this research successfully creates an attractive and memorable identity. The logo is then materialized into a stamp for promotional use. The results demonstrate Warung Lesehan 12's commitment to enhancing their brand image.